ANALISIS TERHADAP DISPOSISIMATEMATIS SISWA SMK PADA PEMBELAJARAN MATEMATIKA - Nasution, Eline Yanti Putri (IAIN PADANGSIDIMPUAN, 2016)
This article was a qualitative research type grounded theory. The purpose of this study is to analyse mathematics disposition through vocational high students in order to understand students’ disposition on mathematics deeply. This study belongs to post positivism paradigm research. According to ontological side, the reality about students’ mathematics disposition is actually appear on students but not or have not been understood before, it just predictable. Otherwise, according to epistemological side, the prediction about mathematics disposition is needed to be more understood. That’s way qualitative research is needed to overcome students’ negative mathematics disposition. Researcher as the instrument analyse students’ mathematics wisely with using triangulation of the data. This study was implemented in one of the vocational high school in Bandung, west java. The subject of this study is 27 students of XI grade at SMKF Bumi Sliwangi. Based on analysis of the data, the finding is obtained in this study are: (1) SMKF Bumsil has a complete facilities with fresh air and a clean environment, (2) mathematics studying and learning process in the classroom is very optimal and conducive so that it can give a positive attitude in students’ mathematics disposition, (3) based on result of quationaire data, there are 21 students (78%) have a positive attitude in mathematics disposition, although there are 6 students (22%) have a negative attitude in mathematics disposition. We can conclude that most of students of XI grade at SMKF Bumsil have a positive attitude in mathematics disposition.